Biodiesel production potential of microalgae, cultivated in acid mine drainage and livestock wastewater. (15th July 2022) - Ahn, Yongtae; Park, Sanghyun; Ji, Min-Kyu; Ha, Geon-Soo; Jeon, Byong-Hun; Choi, Jaeyoung
Abstract: The adaptability and biofuel production potential of two strains of microalgae isolated and cultivated in livestock wastewater effluent (LWE) with acid mine drainage (AMD) were investigated. The isolated strains of microalgae from samples obtained from LWE and AMD, two microalgal strains ( Nephroselmis sp. KGE2 and Autodesmus obliquus KGE17) were selected based on their growth rate and lipid productivity. The dry cell weight of Nephroselmis sp. KGE2 and Autodesmus obliquus KGE17 after 20 days of cultivation in AMD increased from 0.05 to 0.59 g/L and from 0.05 to 0.55 g/L, respectively. These findings revealed a significant accumulation of fatty acids with increasing AMD content. Nephroselmis sp. KGE2 in LWE with 5% AMD demonstrated a higher growth rate (0.59 ± 0.03 g/L) and fatty acid production (401.5 ± 47.3 mg/L) than Autodesmus obliquus KGE17 with 5% AMD. Additionally, Nephroselmis sp. KGE2 had C16–C18 fatty acid content (92.4%) in LWE with AMD. Biodiesel produced from Nephroselmis sp. KGE2 had a higher cetane number (52.31) and iodine value (88.26 g I2 /100 g oil). Consequently, Nephroselmis sp. KGE2 can be considered a potential candidate for biodiesel production using AMD as an iron source. Graphical abstract: Image 1 Highlights: Microalgae strains were isolated from AMD and LEW. The influence of AMD on microalgal biomass and lipid production was evaluated. Feasibility of WWT and microalgae cultivation was evaluated simultaneously. KGE2 showed high biomass and lipid productivity. KGE2 cultivated in AMD demonstrated high total fatty acid productivity (813.56 mg/g).